2022
DOI: 10.3390/agronomy12030654
|View full text |Cite
|
Sign up to set email alerts
|

The Addition of Saflufenacil to Glyphosate plus Dicamba Improves Glyphosate-Resistant Canada Fleabane (Erigeron canadensis L.) Control in Soybean

Abstract: Glyphosate + dicamba has provided variable glyphosate-resistant Canada fleabane (GRCF) control in glyphosate/dicamba-resistant (GDR) soybean. Previous research has indicated improved GRCF control when a third herbicide was added to glyphosate + dicamba, though research is limited. The objective of this research was to ascertain if the level and consistency of GRCF control can be improved when adding tiafenacil, metribuzin, bromoxynil, pyraflufen-ethyl/2,4-D, 2,4-D ester, halauxifen-methyl or saflufenacil to gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…A herbicide mixture of two or more active ingredients have commonly been applied to increase the efficacy and broaden the herbicide spectrum (Polli et al 2021;Dilliott et al 2022;Gazola et al 2022;Lajmanovich et al 2022). Studies demonstrated that the herbicide saflufenacil was added to a mixture of glyphosate + dicamba and applied pre-planting was the most effective to control glyphosateresistant Canadian horseweed (Erigeron canadensis L.).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A herbicide mixture of two or more active ingredients have commonly been applied to increase the efficacy and broaden the herbicide spectrum (Polli et al 2021;Dilliott et al 2022;Gazola et al 2022;Lajmanovich et al 2022). Studies demonstrated that the herbicide saflufenacil was added to a mixture of glyphosate + dicamba and applied pre-planting was the most effective to control glyphosateresistant Canadian horseweed (Erigeron canadensis L.).…”
Section: Introductionmentioning
confidence: 99%
“…Studies demonstrated that the herbicide saflufenacil was added to a mixture of glyphosate + dicamba and applied pre-planting was the most effective to control glyphosateresistant Canadian horseweed (Erigeron canadensis L.). The increase of Canadian horseweed control was reported from 57 to 92, 93 to 99, and 94 to 99% at 2, 4, and 8 Weeks After Application (WAA), respectively (Dilliott et al 2022). However, another study demonstrated the antagonistic effect of herbicide mixture of metribuzin+halosulfuron and metribuzin+flumioxazin on Chenopodium album L., Amaranthus retroflexus L. and caused injury in potatoes with a 50% effective dose (ED50) of 1.21, 0.54, and 12.23 g ai•ha -1 , respectively (Kalkhoran et al 2021).…”
Section: Introductionmentioning
confidence: 99%